Agro-morphological characterization of yams (Dioscorea sp) of Passoré in Burkina Faso - Tiama, Djakaridia; ZOUNDJIHEKPON, JEANNE; Sawadogo, Nerbewende; Nebie, Baloua; Bationo/Kando, Pauline; SAWADOGO, Mahamadou; Zongo, Jean-didier (My University, 2016)
Yams are monocotyledonous plants adapted to areas where the rainfall is high (≥ 800 mm/year). However the northern part of Burkina Faso where the rainfall is low (400 to 600 per year) produces a particular group of yams adapted to the arid conditions of the province of Passoré. This group commonly called Passoré yams or “yùyà” in the national language “mooré”, has three morphotypes respectively called “waogo”, “boussa” and “nyù”. On the farming area of the “yùyà” in Mia (Arbollé) province of Passoré, 66 accessions were collected. Measured characteristics were focused on the size, the shape and the colors of the leaves, the stems and the tubers. The results of morphological characteristics helped to link the morphotype “waogo” to the Asian crop Dioscorea alata; the morphotype “boussa” to the complex species of African yams Dioscorea cayenensis-D. rotundata and the morphotype “nyù” to the wild African species Dioscorea abyssinica/ D. lecardii/D. sagittifolia. The multivariate analyses (PCA and HAC) associate the “nyù” to long stems and tubers; the “boussa” to heavy short tubers and the “waogo” to long wide leaves. Differences in yield have been observed within all the three groups: 15 to 25 t/ha for the “nyù”; 35.75 to 40 t/ha for the “boussa” and 10 to 19 t/ha for the “waogo”.
Keywords: yam; characterization; yùyà; nyù; boussa; waogo; Passoré; Burkina Faso